ENHANCING EDUCATIONAL PRACTICES: THE ROLE OF RESEARCH IN TEACHERS DEVELOPMENT - Rianugraha, Yose (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
For the last few years, education has become the primary need for people to as it is the education that prepares the learners to cope with his/her future work. Education, whether it is a formal, informal or non formal, is an important part in the process of human being’s development particularly because it includes the teaching and learning of knowledge. Teachers, as the educators play important roles in the process of teaching and learning process to be successful. Yet, it sometimes happens that the teaching and learning process is not as successful as what the teachers expected before. This paper aims to propose the significance of doing research for teachers so that teachers can solve the problems and discover something new in the education field. By doing research, teachers will improve their teaching proficiency so that it will promote the teaching and learning process in the classroom.